Understanding hardness evolution of Zr–Si–N nanocomposite coatings via investigating their deformation behaviors. Issue 14 (November 2016) - Wu, Z.T.; Qi, Z.B.; Wei, B.B.; Zhang, D.F.; Wang, Z.C.
Abstract: This work investigates microstructure, hardness and deformation behaviors of Zr–Si–N nanocomposite coatings with 0–20.9 at.% Si. Relationship between the hardness evolution and the deformation behaviors of the nanocomposite coatings was discussed as well. Dislocation glides together with microcrack initiation and propagation contribute to the plastic deformation of the nanocomposite coatings. The microcrack propagation along the columnar, yet weak bonded grain boundaries is found to be the primary factor inhibiting the hardness improvement of the Si-free ZrN coating. The Zr0.963 Si0.037 N0.916 coating exhibits the highest recorded hardness of 33.2 ± 1.0 GPa. The amorphous matrix exhibits a high energy of microcrack formation and propagation when the nanocomposite coating is exposed to indenter. The microcracks produced by nanoindentation in the Zr0.963 Si0.037 N0.916 coating preferentially propagate into the ZrN nanocrystals rather than along the grain boundaries. Both effects of grain size refinement and grain boundary strengthening result in the hardness improvement.